Esophageotracheas Fistula Secondary to a Buttom Battery Ingestion - Al-Turaiki, MD, Dr. Muath; Alqahtani, Dr. Saad; Alsaadi, Dr. Saud Hussein (International Journal of Innovative Research in Medical Science, 2017)
This is a case of 2 years and 6 months girl who has been suffering from shortness of breath, vomiting and dysphagia with solid food since one month. She was diagnosed initially in a local hospital with hyperactive air way disease and given sulbutamol with minimal improvement. One day prior to presentation to our hospital she was eating (olives) then she aspirated, get chocking and developed cardiac arrest. CPR done in the local hospital and we have received her intubated. Investigations and interventional procedures including a chest X-ray showed a total collapse of the right lung due to a round foreign body occluding g right main bronchus which was removed via a bronchoscopy with round metalic foreign body consisting with a button battery in the upper esophagus which was removed by oesophoscopy with communication with trachea. This child would not have developed serious complications such esophagotracheal fistula if the foreign body had been identified and removed early on.